Prevalence and potential relevance of hyperuricemia in pediatric kidney transplant recipients—a CERTAIN registry analysis. (9th March 2022) - Ehren, Rasmus; Habbig, Sandra; Krupka, Kai; Ernst, Angela; Bald, Martin; König, Sabine; Murer, Luisa; Özçakar, Zeynep Birsin; Pohl, Michael; Babenko, Nadezhda; Spartà, Giuseppina; Staude, Hagen; et al.
Abstract: Background: Asymptomatic hyperuricemia is frequently observed in pediatric kidney transplant recipients; symptomatic hyperuricemia, however, is a rare complication. Only few data are available in this patient population. We, therefore, investigated the prevalence of hyperuricemia and its association with kidney transplant function and blood pressure in a multicenter cohort of pediatric kidney transplant recipients. Methods: This is a retrospective, observational multicenter registry study. All pediatric kidney transplant recipients in the CERTAIN database with at least one documented serum uric acid level and a follow‐up of 5 years posttransplant were eligible. We identified 151 patients with 395 measurements of serum uric acid. We calculated the prevalence of hyperuricemia, analyzed potential risk factors and clinical consequences such as elevated blood pressure and reduced estimated glomerular filtration rate (eGFR). Statistical analysis was performed using IBM SPSS Statistics 26. Results: One hundred and ten of 395 (27.8%) serum uric acid levels were above 416 µmol/L (7.0 mg/dL), defined as the upper limit of normal. Univariate analysis showed a significant ( p = .026) inverse association of serum uric acid with eGFR overtime. There was no significant association of serum uric acid concentrations with body mass index (z‐score), blood pressure (z‐score), or sex. No episodes of gout were documented. Conclusion: This study shows that hyperuricemia is present in a considerable number of patients sometime after pediatric kidney transplantation and is associated with lower eGFR. Whether hyperuricemia contributes to faster decline of graft function or to the overall cardiovascular risk of these patients remains to be elucidated.